Respuesta :

[tex](y^7)^3 = y^{7+3} = y^{21}.[/tex]
y-7) (y+6) =
Simplifying
(y + -7)(y + 6) = 0

Reorder the terms:
(-7 + y)(y + 6) = 0

Reorder the terms:
(-7 + y)(6 + y) = 0

Multiply (-7 + y) * (6 + y)
(-7(6 + y) + y(6 + y)) = 0
((6 * -7 + y * -7) + y(6 + y)) = 0
((-42 + -7y) + y(6 + y)) = 0
(-42 + -7y + (6 * y + y * y)) = 0
(-42 + -7y + (6y + y2)) = 0

Combine like terms: -7y + 6y = -1y
(-42 + -1y + y2) = 0

Solving
-42 + -1y + y2 = 0

Solving for variable 'y'.

Factor a trinomial.
(-6 + -1y)(7 + -1y) = 0
ACCESS MORE